Quenching‐circumvented ergodicity in relaxor Na1/2Bi1/2TiO3‐BaTiO3‐K0.5Na0.5NbO3. Issue 7 (18th February 2021) - Wei, Qiumei; Riaz, Adeel; Zhukov, Sergey; Hofmann, Kathrin; Zhu, Mankang; Hou, Yudong; Rödel, Jürgen; Kodumudi Venkataraman, Lalitha
Abstract: Quenching alkaline bismuth titanates from sintering temperatures results in increased lattice distortion and consequently higher depolarization temperature. This work investigates the influence of quenching on the ergodicity of relaxor Na1/2 Bi1/2 TiO3 ‐BaTiO3 ‐K0.5 Na0.5 NbO3 . A distinct departure from ergodicity is evidenced from the increase in remanent polarization and the absence of frequency dispersion in the permittivity response of poled samples. Further, the samples exhibit enhanced negative strain upon application of electric field, indicating proclivity towards correlated polar nanoregions, corroborated by the enhanced tetragonal distortion. As a result, ergodic relaxor Na1/2 Bi1/2 TiO3 ‐6BaTiO3 ‐3K0.5 Na0.5 NbO3 exhibits a depolarization temperature of 85°C with a 60% increase in remanent polarization and approximately a threefold increase in remanent strain upon quenching. Quenching‐induced changes in the local environment of Na + and Bi 3+ cations hinder the development of ergodicity promoted by the A‐site disorder. These results provide new insight into tailoring ergodicity of relaxor ferroelectrics.